Influence of Ag NPs on Silicon Nanocolumns NH3 Gas Sensors. Issue 14 (20th November 2018) - Hashim, Duaa A.; Alwan, Alwan M.; Jawad, Muslim F.
Abstract : Two NH3 gas sensor devices, Al/Si nanocolumns/n-Si/Al and Al/Ag NPs/Si nanocolumns/n-Si/Al hybrid structures, have been fabricated and tested. A bare silicon nanocolumns layer was synthesized by a laser-assisted electrochemical etching process in HF solutions. The surface morphology of bare Si nanocolumns was modified by incorporating Ag NPs into Si nanocolumns by simple and fast immersions methods in an aqueous solution of AgNO3 to synthesize a hybrid structure. Characteristic features of bare Si nanocolumns and hybrid structure were investigated using scanning electron microscopy, EDS analysis, FTIR spectra, X-ray diffraction, and photoluminescence spectra (PL). The electrical characteristics of sensors with and without NH3 gas were measured at room temperature. The results showed that the nanoparticles grain size, nature, specific surface area (S.S.A) of Ag NPs, and morphological structure of the Si nanocolumns strongly affected the property characteristics. A significant enhancement in sensitivity, response, and recovery times of gas sensor for a hybrid structure was realized after compared with Al/Si nanocolumns/n-Si/Al gas sensor due to the high specific surface area.